Chapter News from the Invisible World The Publishing History of Tales of the Supernatural c.1660-1832 - Barry, Jonathan (Springer Nature, 2017)
This chapter explores the transmission of tales of the supernatural during the very long eighteenth century (between c.1660 and c.1832). A genre of publications on this subject which have not been studied are those anthologies of supposedly true stories, usually relating to named people and places and sometimes dated, often each numbered separately, with relatively little discussion of their authenticity or significance, beyond perhaps a brief preface defending the reality of the world of spirits. A series of entrepreneurial publishers, mostly operating from Paternoster Row in London, experimented with anthologising these stories in varied combinations. Any attempt to analyse the stories must begin by unravelling the publishing history by which they were transmitted and (not fully studied here) modified and retold, as well as re-interpreted.